2021
DOI: 10.3390/w13040499
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Rainy and Dry Season Per Capita Water Consumption in Freetown City Sierra Leone

Abstract: Ensuring a sustainable urban water supply for developing/low-income countries requires an understanding of the factors affecting water consumption and technical evidence of individual consumption which can be used to design an improved water demand projection. This paper compared dry and rainy season water sources available for consumption and the end-use volume by each person in the different income groups. The study used a questionnaire survey to gather household data for a total of 398 households, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…It indicated that people should drink at least 2 L water a day for a healthy and balanced diet, because water helps the digestive system to work better and cleans the blood by removing harmful chemicals and toxins from the body, is the main substance and vitality source in all physiological functions in the body, makes the skin beautiful, and helps people to lose weight. Previous researches, therefore, declared that men and women should drink 3 and 2.5 L water , respectively (Cuvelier and Bartell, 2021;İbrahim et al, 2021). Explaining the physiological effects of drinking water on human health in all its dimensions, Mukate et al (2019) evaluated the direct and indirect effects of various problems of unsuitable drinking of water in human physiology with many dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that people should drink at least 2 L water a day for a healthy and balanced diet, because water helps the digestive system to work better and cleans the blood by removing harmful chemicals and toxins from the body, is the main substance and vitality source in all physiological functions in the body, makes the skin beautiful, and helps people to lose weight. Previous researches, therefore, declared that men and women should drink 3 and 2.5 L water , respectively (Cuvelier and Bartell, 2021;İbrahim et al, 2021). Explaining the physiological effects of drinking water on human health in all its dimensions, Mukate et al (2019) evaluated the direct and indirect effects of various problems of unsuitable drinking of water in human physiology with many dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…where Q peak represents the peak water consumption (in liters per second); this quantity is also known as the Maximum Hourly Flow in the criteria for design or specifications of some countries [26]. Q avg denotes the average water consumption during non-peak periods (in liters per second).…”
Section: Peak Water Consumptionmentioning
confidence: 99%
“…As the fluctuations in the block-wise customers were observed, the water consumption patterns also depicted seasonal variations. This may be due to more frequent water consumption activities such as showering and washing during summer [32].…”
Section: Block-wise Water Consumptionmentioning
confidence: 99%